OPTOELECTRONIC SENSORS - Xakimov Temur; Toshtemirov is the son of Shohruh Uktam (Лучшие интеллектуальные исследования, 2024)
Abstrackt: Examples of fiber optic applications include environmental and atmospheric monitoring, earth and aerospace sciences, industrial processing and biotechnology, digital imaging, and other fields. Optical fiber sensors differ in their small size and long-term operation. At the same time, the electromagnetic interference, multiplexing capability and high sensitivity of optical fibers also include the aerospace field. We will consider that fiber optic sensors also provide a wide range of applications for addressing electrical and electronic sensors and performing high-level sensing tasks. This article shows that the use of optical fiber sensors is effective.